ACTION EFFICIENCY ESTIMATION OF ANTI-ICING ADDITIVES FOR AVIATION FUELS - A. V. Oreshenkov; N. N. Grishin (Научный вестник МГТУ ГА)
The questions of action efficiency estimation of anti-icing additives are considered. The description of qualifying estimation methods and norm of defined parameters efficiency is resulted.